ANALYSIS OF BUSINESS FEASIBILITY STUDY ON SPICYPEDIA MSME DEVELOPMENT - Rio Era Deka; Irlina Dwi Evasoyaningrum; Novita Dwi Pratiwi; Dea Vidia Fransisca; Helmi Artika Sari; Imelda Maulinda; Nadya Aprillia Salsabila (International Journal of Entrepreneur and Business Administration, 2023)
The purpose of this study is to determine the business feasibility of the Spicypedia UMKM. The method used in this research is qualitative and quantitative with analysis of 7 aspects studies appropriateness business Which covers aspect law, aspect marketing, aspect technical, social economic aspects, management/organizational aspects, environmental aspects and financial aspects. The technique of collecting data in this study is by observing objects at the company, documentation, and direct interviews with the parties concerned. Results analysis aspect law state that Not yet worthy, whereas For 6 aspect other show results Which positive that business Which done by UMKM Spicypedia is worth doing.